PENGARUH KEPRIBADIAN, MOTIVASI TERHADAP KINERJA GURU DIMEDIASI KEDISIPLINAN ( Studi pada SD Islam Sultan Agung Semarang ) (Students' Journal of Economic and Management, 2012)
The Study aims to examine the influence of personality and motivation to teacher performance mediated by  discipline. The specific objectives of this study are to examine the role of discipline mediated influence of personality and motivation. This study used a sample on teachers elementary school who are on the Foundation Board of Waqf Sultan Agung in Semarang. as much as 116teacher. This study examined the direct and indirect relations between influence of personality and motivation to teacher performance mediated by discipline The results show that Personality has positive impact to discipline, Motivation has positive impact to discipline, Personality has not positive impact to teacher performance. Motivasi has positive impact to teacher performance. Discipline has positive impact to teacher performance. Keywords: Personality, motivation, discipline and teacher performance